The determinant of Audit Quality Based on Internal Audit Capability Model (IACM) - S. Hastuti; R. P. Sari; O. Tannar (Nusantara Science and Technology Proceedings)
The purpose of this study was to determine the effect of Competence, Independence, Compliance Obedience and Internal Control System (SPI) on the quality of audit results based on Internal Audit Capability Model (IACM). This study contributes theoretical and practical benefits as a form of adoption of agency theory and attribution theory and suggestions for improving auditor expertise about competence, independence, and compliance pressure to produce quality checks in the field of supervision. This study uses a quantitative approach. The analysis technique used in this study is Partial Least Square with the help of PLS warp software. The subject of this study was the Inspectorate of East Java Province with a sample of auditors in the Inspectorate of East Java Province, amounting to 53 auditors. The results of this study indicate that the Competency and Internal Control System affect the Quality of Audit Results based on Internal Audit Capability Model (IACM), while Independence and Pressure of compliance do not affect the Quality of Audit Results based on Internal Audit Capability Model (IACM).